1987
DOI: 10.1002/hep.1840070125
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of antimitochondrial antibodies in primary biliary cirrhosis before and after orthotopic liver transplantation

Abstract: Antimitochondrial antibodies are markers for primary biliary cirrhosis and probably reflect a specific defect in immunoregulation underlying this disease. Antimitochondrial antibodies and their primary biliary cirrhosis-specific subtypes were tested before and up to 6 years after orthotopic liver transplantation. Sera from 31 consecutive patients were tested, 15 patients had primary biliary cirrhosis and 16 non-primary biliary cirrhosis. Antimitochondrial antibodies were investigated under code by immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 17 publications
1
15
1
Order By: Relevance
“…Our experience suggests that truly recurrent disease is quite unusual. Similar results were reported by Haagsma et al (20), who found no evidence of recurrence of PBC in 9 liver transplant recipients followed for at least 1 yr. Attention to the fine details of the type of inflammatory cells found mostly in the portal areas, the degree to which these cells infiltrate the surrounding parenchyma, and the presence or absence of subintimal foamy macrophages and true cirrhosis (regenerative nodules and fibrosis) apparently make it possible to distinguish between these two entities.…”
Section: Discussionsupporting
confidence: 91%
“…Our experience suggests that truly recurrent disease is quite unusual. Similar results were reported by Haagsma et al (20), who found no evidence of recurrence of PBC in 9 liver transplant recipients followed for at least 1 yr. Attention to the fine details of the type of inflammatory cells found mostly in the portal areas, the degree to which these cells infiltrate the surrounding parenchyma, and the presence or absence of subintimal foamy macrophages and true cirrhosis (regenerative nodules and fibrosis) apparently make it possible to distinguish between these two entities.…”
Section: Discussionsupporting
confidence: 91%
“…ei~her this series (13) or that of Haagsma et a1. (23). SImIlarly, no apparent correlation between the AMA titers and presence of chronic rejection was seen in this study.…”
Section: Pathologic Comparison Of Native Hepatectomies With Pbc and Fcontrasting
confidence: 61%
“…Thus, in approximately 80% of patients with PBC with cadaveric grafts, AMA was detectable after transplantation, although titers decreased steeply, particularly during the first year. [2][3][4]7,9,16,17 We were unable to evaluate a possible difference between patients with grafts from blood relatives versus grafts from non-blood relatives because we had only 1 patient with a graft from a non-blood relative. She was positive for AMA and anti-PDC-E2 before LLT, but had multiple HLA matches.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common indications for adult LLT is primary biliary cirrhosis (PBC). Based on experience with cadaveric liver transplantations, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] PBC must be expected to recur in some of these patients. Recurrence of PBC in allografts is suspected when such immunologic abnormalities as antibodies against mitochondrial components and increased immunoglobulin M (IgM) concentrations persist and extrahepatic manifestations of PBC develop or fail to recede.…”
mentioning
confidence: 99%